Cylindrical Osteochondral Allograft for Osteochondral Lesions of the Talus: A Systematic Review. Issue 1 (January 2022) - Azam, Mohammad; Davey, Martin S.; Colasanti, Christopher; Mercer, Nathaniel P.; Hurley, Eoghan T.; Shimozono, Yoshiharu; Kennedy, John G.
Category: Ankle Introduction/Purpose: Ankle injuries commonly result in damage to the articular cartilage of the talus. The use of cylindrical osteochondral allografts (OCA) for osteochondral lesions of the talus (OLT) smaller than 1.5cm is increasingly common, particularly in cases whereby autologous osteochondral transplantation (AOT) is contraindicated. The primary aim of this study is to systematically review the outcomes of cylindrical OCA for OLT. The secondary aim of this study is to compare the outcomes of cylindrical OCA and AOT in the management of similar cases of OLT. Methods: Two independent reviewers searched the literature based on PRISMA guidelines, utilizing the EMBASE, MEDLINE, and The Cochrane Library Databases. Only studies that reported outcomes of cylindrical OCA in the management of OLT were included. Results: Overall, 4 studies with 100 patients including 101 ankles were included in this review. Pre-operative OLT characteristics showed 69.3% of OLT lesions were located medially, with a mean lesion size of 1.47cm 2 (0.46 - 4.2 cm 2 ). Overall, 16.8% of ankles required surgical revision following cylindrical OCA; 1.0% (1/101) underwent subsequent arthrodesis, 6.9% (7/101) underwent revision osteochondral grafting and 7.9% (8/101) underwent subsequent arthroscopic debridement. Radiological outcomes between the graft failure were reported as 10.0% (3/30), joint space narrowing as 30.4% (14/46), and cysts as 42.9% (27/63). Significantly higher revision rates were reported following cylindrical OCA when compared to AOT at over two years follow up (28.1% versus 6.7%, p = 0.02). Conclusion: Our systematic review established that although there are high rates of patient satisfaction following cylindrical OCA for OLT, these are less than those reported with AOT for the same condition. Concerns regarding the rates of radiological deterioration as well as the need for surgical revision may represent harbingers for poorer long-term outcomes.